Contracting with Researchers - Matthias Verbeck (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
We study a setting in which one or two agents conduct research on behalf of a principal. The agents binary performance level (suc- cess or failure) depends on their invested research e ort, and their choice of a research technology that is uncertain in respect of its apt- ness to generate a success. While in the single-agent-setting the agent has no incentive to deviate from the principal s preferred technology choice, this is not generally true for the multiagent-setting. When technologies are mutually exclusive - only one of them will be suit- able for yielding a high output - we show that there exists a contract that aligns the principal s and the agents interests. However, under the plausible assumption of scientists free technology choice, our re- sults suggest that there is a bias towards mainstream-research: Agents choose promising technologies more often than socially optimal.
Keywords: D82; D86; D83; 330